"She's just like me": The Role of the Mentor with Vulnerable Mothers and their Infants. (14th April 2015) - Mitchell, Gaye; Absler, Deborah; Humphreys, Cathy
<x content-type="archive" xml:space="preserve">Abstract</x> Mentoring Mums, a community-based pilot program, exemplifies a model of volunteer home visiting to vulnerable and socially isolated new mothers and their at-risk infants. An evaluation of the program found that positive changes for both mothers and their babies had been achieved, providing the rationale for exploration of elements that made the mentoring role effective. This article undertakes this exploration through the research question: What do mothers, mentors and workers contribute to the conceptualisation of the mentor role with vulnerable mothers and their infants? The article argues that the program's effectiveness resided in a mentor role that shared primary values of befriending and neighbourliness, rather than in mentors enacting a quasi-professional role. Conceptualisation of the mentor role is based in theory and practice, seeing mentors as straddling the formal world of service intervention and the informal world of kith and kin. It presents 'befriending' as part of building substitute networks around very isolated new mothers. The very significant problems experienced by these vulnerable mothers made necessary parallel involvement of a professional volunteer coordinator and ongoing case management. Mentoring did not replace professional involvement, but rather was distinguished as providing something different, but much needed for vulnerable new mothers and their babies.